Managing the Impact of Climate Change on Migration: Evidence from Mexico - Isabelle Chort; Maëlys de la Rupelle (Global Labor Organization (GLO), 2017)
This paper uses state-level migration ow data between Mexico and the U.S. from 1999 to 2011 to investigate the migration response to climate shocks and the mitigating impact of an agricultural cash-transfer program (PROCAMPO) and a disaster fund (Fonden). Our results suggest that lower than average precipitations increase undocumented migration, especially from the most agricultural states. Fonden amounts are found to mitigate the effect of climate shocks on migration by lowering the undocumented migration response to precipitation anomalies. Similarly an increase in the state-level share of PROCAMPO funds to non-irrigated plots in the ejido sector decreases migration after a shock.
Keywords: F22; Q54; Q18; O15; J61; 330; International migration; Climate change; Public policies; Weather variability; Natural disasters; Mexico-U.S. migration